Integrasi Sistem Internal sebagai Pembentuk Kapabilitas Organisasi UMKM Kuliner di Indonesia - Kurnia, Fikrihadi; Fitri, Yelli (Metode : Jurnal Teknik Industri, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector play a strategic role in the national economy; however, many still face limitations in managing internal business systems. This study aims to analyze how the integration of financial management, human resource management, and supply chain and distribution systems shapes the organizational capabilities of culinary MSMEs. A qualitative approach with a multiple-case study design was employed, involving two culinary MSMEs operating around Universitas Mataram and the Kekalik District. Data were collected through in-depth interviews, direct observation, and document analysis, and examined using thematic analysis and cross-case comparison. The findings indicate that MSMEs with more integrated internal systems demonstrate higher operational stability and stronger market adaptability than those with fragmented systems. Cross-functional integration emerges as a critical determinant in building MSME organizational capabilities. These results suggest that even basic and informal forms of system integration can substantially enhance the resilience and long-term sustainability of culinary MSMEs. This study highlights the importance of a systemic approach to MSME development in supporting long-term business sustainability.